Factors Affecting the Early Initiation of First Antenatal Care Visit among Pregnant Women in Bangladesh: A Multiple Logistic Regression Analysis - Reshmi, Mst Farzana Akter; Asad, Asadujjaman; Ali, Md Sagor; Barman, Sourav Kumar; Setu, Sarmistha Paul; Islam, Md Ariful; Hossain, Md Golam (International Journal of Statistical Sciences, 2025)
Antenatal care (ANC) is essential for improving maternal and child health outcomes by reducing mortality and malnutrition. In countries with higher maternal mortality and morbidity rates, the timely initiation of antenatal care (ANC) is essential. However, a substantial proportion of women delay the commencement of ANC visits beyond the recommended period. This study investigates the prevalence of early initiation of the first ANC visit among pregnant women in Bangladesh and explores the associated risk factors influencing the timing of ANC utilization. The analysis is based on cross-sectional data from the 2017–2018 Bangladesh Demographic and Health Survey (BDHS). In this present study, total 4,451 pregnant women were involved. The study employed chi-square tests and a multiple binary logistic regression model to identify factors associated with the early initiation of the first ANC visit. The objective was to determine the key predictors contributing to the first ANC visit among pregnant women in Bangladesh. Results exposed that 41.6% of pregnant women introduced their first ANC visit within the suggested timeframe. The regression analysis identified several statistically significant predictors of early ANC initiation, including place of residence (p < 0.05), women’s education level (p < 0.01), household wealth index (p < 0.05), age at first birth (p < 0.05), birth order number (p < 0.05), husband’s education level (p < 0.01), media access (p < 0.01), and division (p < 0.05). These results highlight the need for targeted public health policies and interventions to promote timely ANC initiation and improve maternal healthcare utilization in Bangladesh. IJSS, Vol. 25(1), March, 2025, pp 71-86